Essays in Keynesian persuasion - Marcuzzo, Maria Cristina, 1948- (Cambridge Scholars Publishing, 2019)
This collection of essays of provides a comprehensive and detailed account of several aspects of the Cambridge School of Economics, which featured a number of outstanding figures such as Keynes, Sraffa, Kahn, and Joan Robinson. Scholars interested in heterodox economics, the history of economic thought and political economy will find in this book the Keynesian leitmotivs--the fight against unemployment, and the roles of money and uncertainty--which make Keynes's legacy relevant for today's world. The contributions here are written in the spirit of Keynes, and are persuasive and accessible to t.